2021
DOI: 10.1016/j.eswa.2021.114920
|View full text |Cite
|
Sign up to set email alerts
|

Gradient-based grey wolf optimizer with Gaussian walk: Application in modelling and prediction of the COVID-19 pandemic

Abstract: This research proposes a new type of Grey Wolf optimizer named Gradient-based Grey Wolf Optimizer (GGWO). Using gradient information, we accelerated the convergence of the algorithm that enables us to solve well-known complex benchmark functions optimally for the first time in this field. We also used the Gaussian walk and Lévy flight to improve the exploration and exploitation capabilities of the GGWO to avoid trapping in local optima. We apply the suggested method to several benchmark functions to show its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 69 publications
0
29
0
1
Order By: Relevance
“…Since Michael E. Porter put forward the value chain theory, the optimization and operation of the value chain have been widely concerned by scholars. They mainly discuss evolution trend forecasting, site selection, logistics transportation optimization, purchasing and inventory optimization, product portfolio optimization and sustainable development in the value chain [7,8,15,16,23,41,9,17,11,26,13,14,10,32,27,28]. For example, by using artificial intelligence tools, Goli et al [7] established a multi-stage model to study the evolution trend of demand for dairy products and found that demographic behavior and inflation rate are the main factors affecting dairy consumption.…”
Section: Literature On the Optimization And Operation Of The Value Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Michael E. Porter put forward the value chain theory, the optimization and operation of the value chain have been widely concerned by scholars. They mainly discuss evolution trend forecasting, site selection, logistics transportation optimization, purchasing and inventory optimization, product portfolio optimization and sustainable development in the value chain [7,8,15,16,23,41,9,17,11,26,13,14,10,32,27,28]. For example, by using artificial intelligence tools, Goli et al [7] established a multi-stage model to study the evolution trend of demand for dairy products and found that demographic behavior and inflation rate are the main factors affecting dairy consumption.…”
Section: Literature On the Optimization And Operation Of The Value Chainmentioning
confidence: 99%
“…[15]; Khalilpourazari et al[16]; Lotfi et al[23]; Tirkolaee et al[41];Goli et al [9][17]; Goli et al[11]; Lotfi et al[26]; Khalilpourazari et al[13]; Khalilpourazari et al[14]; Goli et al[10]; Pahlevan et al[32]; Lotfi et al[27]; Lotfi et al[28] …”
mentioning
confidence: 98%
“…The findings disclosed that the proposed model can render a proper approximation of COVID-19 trend. By using gradient-based grey wolf optimizer, Khalilpourazari et al ( 2021 ) have published a study concerning COVID-19 prediction. First, they compared their algorithm with some benchmark algorithms and concluded that the proposed model is more accurate.…”
Section: Literature Surveymentioning
confidence: 99%
“…Her problem tipine göre en başarılı algoritmanın değişmesi, yeni meta-sezgisel algoritmaların oluşturulmasına ya da mevcutların geliştirilmesine imkan tanır. Literatürde optimizasyon algoritmalarının geliştirilmiş (iyileştirilmiş) versiyonları ile ilgili [2][3][4][5], algoritmaların birleştirilmesi ile oluşturulan hibrit algoritmalar [4][5][6][7][8][9] ile ilgili ya da yeni oluşturulan algoritmalarla ilgili çalışmalara rastlamak mümkündür.…”
Section: Introductionunclassified